Management of stress incontinence in older women - Karolina Kubiak; Jakub Husejko; Małgorzata Gajos; Oktawia Wysocka; Martyna Lamtych; Aleksandra Modlińska; Joanna Sarnowska; Patryk Gaborek; Natalia Krakowska; Miłosz Kankowski; Kornelia Kędziora-Kornatowska (Kazimierz Wielki University, 2019)
Introduction: Stress incontinence is a problem increasingly affecting older people. This discomfort has an impact on women as a greater extent. Stress urinary incontinence is described as involuntary leakage of urine during even minor efforts: sneezing, coughing, rapid gait. At the beginning inconspicuous loss of a few drops of urine is often not alarming for women. The problem is significant because women often go to a specialist very late and the reason for this is shame. Many people think that this is an accident of old age and it can't be stopped. Nothing could be more wrong, it can be dealt with. Material and methods: Articles in the EBSCO database have been analysed using keywords: stress incontinence, problems of old age, physiotherapy in urology, older women. Results: The incidence of stress incontinence in women increases with age. The main reason is muscular weakness, which is caused, among other things by pregnancies and labours. Another reason may be hormonal disorders and genetic predisposition. Statistics show that obese women are more likely to suffer from SUI. The progress of medicine and pharmacology is also increasingly effective in the treatment of stress urinary incontinence. First, after finding the problem, conservative treatment is introduced. Treatment is adapted to each patient individually. Age, existing diseases, weight are important factors in the process of treatment. In pharmacology Duloxetine is used. The use of this drug does not completely eliminate the symptoms of stress urinary incontinence. Due to the possibility of side effects i.e. nausea, the drug is used very carefully. In recent years, physiotherapy has been highly valued in the treatment of stress urinary incontinence. The most important is kinesitherapy here. Strengthening the pelvic floor muscles brings the most beneficial effects. Active exercises are supported by: electrostimulation, magnetotherapy and vibro-therapy. The final form of SUI treatment is surgical treatment. However, this do not always bring the expected results. In order to increase the effectiveness of therapy for patients with SUI, the interdisciplinary cooperation of the medical team should be used. Treatment of stress urinary incontinence primarily leads to improved quality of life for patients. Conclusions: Urinary incontinence is a social disease. Women struggle with this problem twice as often than men. Stress incontinence accounts for 63% of all forms of urinary incontinence in women in Poland. The incidence of incontinence increases with age. Problems with stress urinary incontinence become a reason for isolation from society. The patients are not aware of the treatment possibilities, which often results in late inclusion of treatment and rehabilitation. There is a wide range of SUI treatment options. Therefore it is necessary to personalise rehabilitation process to best fit to each patient. Keywords: stress incontinence, problems of old age, physiotherapy in urology, older women.